Implementation of Foreign Experiences to Develop Wine Tourism in Samarkand Region - Rakhmonov Shukhrat Shavkatovich (Universitas Muhammadiyah Sidoarjo, 2020)
Tourism is one of the most significant sectors of the world economy and a catalyst to the development of the economy of both local and international markets. World Travel and Tourism Councils reported that travel and tourism made up 10.4 % of global GDP. Wine tourism has become one of the popular tourism markets for the last few decades. This article depicts the definition of wine tourism and its relation with other types of tourism. Moreover, the article analyzes statistics on world wine production and top 10 countries on wine tourism and discusses the implementation of their experiences to develop wine tourism in Samarkand region.